Desain dan Pengembangan Website untuk Mendeteksi Malware Menggunakan Framework Flask yang Diintegrasikan dengan Machine Learning - Ciksadan, Ciksadan; Soim, Sopian; Jami, Nurlita (Program Studi Teknik Informatika Universitas Pamulang, 2024)
One of the most widely used media for information dissemination is the website. A dynamic and informative website will make it easier for users to access information. Web development often requires complex technologies. One method that can simplify the development process is using the Flask framework, which offers flexibility and freedom to developers. A website must also have functionality to be useful; one current issue is the increasing number of malware file cases. Therefore, there is a need for a medium that can analyze a file. However, currently, there are limited services available for this purpose. This research aims to build a website that detects malware files using the Flask framework integrated with machine learning for malware file detection. Through this research, a website with five informative menus has been developed, featuring a dynamic and easily accessible interface with a malware file detection capability reaching 99% accuracy.